Crosstalk Between Autophagy and the cGAS–STING Signaling Pathway in Type I Interferon Production - Zhang, Kunli; Wang, Sutian; Gou, Hongchao; Zhang, Jianfeng; Li, Chunling (Frontiers in Cell and Developmental Biology, 2021)
Innate immunity is the front-line defense against infectious microorganisms, including viruses and bacteria. Type I interferons are pleiotropic cytokines that perform antiviral, antiproliferative, and immunomodulatory functions in cells. The cGAS–STING pathway, comprising the main DNA sensor cyclic guanosine monophosphate/adenosine monophosphate synthase (cGAS) and stimulator of IFN genes (STING), is a major pathway that mediates immune reactions and is involved in the strong induction of type I IFN production, which can fight against microbial infections. Autophagy is an evolutionarily conserved degradation process that is required to maintain host health and facilitate capture and elimination of invading pathogens by the immune system. Mounting evidence indicates that autophagy plays an important role in cGAS–STING signaling pathway-mediated type I IFN production. This review briefly summarizes the research progress on how autophagy regulates the cGAS–STING pathway, regulating type I IFN production, with a particular focus on the crosstalk between autophagy and cGAS–STING signaling during infection by pathogenic microorganisms.